Perlindungan Hukum Hak Cipta Batik Tradisional Di Kota Surakarta - Khomeini, Ilham Mohammad Asngad; , Inayah,S.H., M.H (2017)
Traditional Batik is proptected by Copyrihgt Act As a creation as well as the intellectual property protection and use of knowledge traditional and traditional cultural expression. Society's awareness and comprehension of the applicable copyright law, in particular small and medium industry, is still low. Correct enforcement of Copyright Act and promotion of legal awareness is needed in order to reach a prosperous society.